Gaps in the IFRS Conceptual Framework - Barker, R; Teixeira, A (Routledge, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.